IMPLEMENTASI AUDIT MUTU INTERNAL ISO 9001 PADA SISTEM MANAJEMEN RSUD KAYU AGUNG KABUPATEN OKI - Fransisca, Septiani; Aliya, Sabeli (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
Many companies have implemented ISO 9001 but no research has focused on the factors that made up the internal audit quality variables. This research took place at the Rumah Sakit Umum Daerah of Kayu Agung of Ogan Komering Ilir Regency. This research used quantitative descriptive method. The population was stakeholders related to the entity, the sample used cluster sampling and simple random sampling. The data used primary data derived from the dispersed questionnaire. The distribution of questionnaire was conducted in 2018. The technique of data analysis used validity test, profitability test, and normality test. In analyzing the researchers used simple linear regression analysis. The calculation results showed the value of R Square was 0.629. This meant that 62.9% of the Kayu Agung Hospital Management System in Ogan Komering Ilir Regency was influenced by the ISO 9001 Internal Quality Audit.